CATALYTIC ACTIVITY OF ZSM-5 ZEOLITE LOADED WITH TRANSITION METALS FOR THE SELECTIVE CATALYTIC REDUCTION OF NOX - I.M. Saaid; A.R. Mohamed; S. Bhatia Bhatia (ASEAN Journal on Science and Technology for Development, 2002)
Catalytic activity measurement were carried out on catalysts formulated from ZSM-5 zeolite separately loaded with transition metals (Cu, Co, Ni, Fe) for the removal of NOx in simulated diesel exhaust conditions. Various factors were investigated to compare the performance of these catalysts including catalyst preparation method, Si/Al ratio of the parent zeolite support, and durability in the exhaust stream containing water vapor or SO2. In many experimental conditions except in the presence of water vapor or SO2, Cu-ZSM5 remained the most active catalyst with 100% NOX conversion at around 350°C. C0-ZSM5 and Ni-ZSM5 could also achieve complete NOx conversion but at a much higher temperature of around 450°C. Fe-ZSM5 catalyst was the least active catalyst probably due to the formation of iron oxide particle, which accelerated formation of carbon monoxide.